Pembelajaran Sejarah Kebudayaan Islam sebagai Media Penanaman Nilai-nilai Multikultural pada Siswa - Muhammad Alwi Batubara; Febriyanti Dmaranti Nasution; Ayu Lestari Simbolon; Ilpa Hasanah (Prodi Pendidikan Keagamaan Islam, 2022)
This study aimed to understand how the learning process of Islamic Cultural History (SKI) was used as a medium for instilling multicultural values in students, the supporting and inhibiting factors involved, as well as the outcomes of the learning process. This study used a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The research subjects included SKI teachers and students of MTs Darul Ikhlas Dalan Lidang. The results showed that SKI learning at MTs Darul Ikhlas Dalan Lidang had played an important role as a medium for instilling multicultural values such as tolerance, mutual respect, and cooperation. The learning process was carried out through various methods, including lectures, discussions, and teacher modeling that connected Islamic historical values with students’ daily lives. Supporting factors in this learning included the school's support, students’ enthusiasm, a diverse environment, and engaging teaching methods. Meanwhile, inhibiting factors included limited time, lack of learning media, and differences in student character. In conclusion, SKI learning at MTs Darul Ikhlas Dalan Lidang was essential in fostering multicultural values, as teachers did not only teach historical knowledge but also embed moral and social values relevant to students’ lives.